Will tropical dry forests be vulnerable to climate change, and what will be their social effects? (UNED Research Journal, 2019)
Tropical dry forests provide societies with many valuable ecosystem services. These forests are characterized by alternating rainy and dry seasons. Changes to rainfall regimes are likely to negatively impact the internal dynamics of dry forests; at longer timescales, climate change may shift the geographical borders of dry forests. Society should establish policies and management practices such as reforestation with drought tolerant tree species to adapt to these changes now.
Keywords: climate change; dry tropical forest; ecosystem services; adaptation